Variasi Bahasa Indoglish dan Idiolek Publik Figur di Instagram - Afifah Nuur Qory'ah; Agus Tika Dwi Savira; Elen Inderasari (TRANSFORMATIKA, 2019)
This study aims to describe the language variation phenomena in the form of indoglish and idiolect in the Girl Squad public figures on Instagram social media. This research is qualitative research with a qualitative descriptive method. The data in this study are in the form of captions or written expressions on Girl Squad’s Instagram uploads. Data sources were obtained from public social media Instagram of Girl Squad member figures. Data collection techniques are collected through documentation, listening, and note-taking. Data analysis was carried out in the interactive study by classifying data taken in written expressions on the Instagram caption of Girl Squad members who then organized and concluded indoglish languages and Idioms. The result of this study indicates the indoglish phenomenon that occurs in the upload of written expressions on the public Instagram figure of Girl Squad. Also, idiolect was found in several public members of the Girl Squad figure. Indoglish language patterns found include (1) prefix insertions, (2) suffix insertions, and (3) pronouns. Idiolect language patterns found include (1) word emphasis, (2) adaptation, (3) creation or formation of new words, and (4) contemporary language.